Respuesta :
Answer:
X = -2
Step-by-step explanation:
(If you mean to "check the answer" then the answer above mine would help more)
I hope this answer helps. You should show your work as proof:
We simplify the equation first:
18x−2(3x+1)=5x−16
18x+(−2)(3x)+(−2)(1)=5x+−16 (Distribute)
18x+−6x+−2=5x+−16
(18x+−6x)+(−2)=5x−16 (Combine Like Terms)
12x+−2=5x−16
12x−2=5x−16
Then we cancel out:
12x−2−5x=5x−16−5x
7x−2=−16
7x−2+2=−16+2
7x=−14
7x/7 = −14/7
x = -2
The solution to the expression, 18x-2(3x+1)=5x-16 is; x =2.
To prove that 18x-2(3x+1)=5x-16 holds for x = -2.
We must solve the equation for x as follows;
- 18x-2(3x+1)=5x-16
- 18x -6x -2 = 5x -16
By collecting like terms;
- 7x = -14
x = -2
Read more:
https://brainly.com/question/1640242